India's social policies: Recent changes for the better and their causes - Joachim Betz (German Institute of Global and Area Studies (GIGA), 2019)
Despite being a consolidated democracy with free and fair elections and having a political system with intense party competition, a relatively vibrant civil society, and a functioning federal set-up, India still ranks poorly in terms of the coverage, generosity, efficiency, and quality of its social protection. This is difficult to explain based on the factors usually advanced for the implementation of generous social policies. A second puzzle is the predominantly protective nature of welfare policies in India in the current era of globalisation, which should necessitate policies enabling workers to participate successfully in a more demanding economic environment. These puzzles may be explained partly by (a) the long-term insulation of the Indian economy from international competition, (b) the low share of industry and modern services in GDP until recently, (c) the precedence of identity policies, (d) the fragmentation of the political sphere, and (e) the meagre empowerment of women in India. We should, however, acknowledge that change is underway and that the picture is not bleak across India as a whole - being supported by economic reforms and growth, a greater degree of decentralisation and party competition within the country, increasingly discerning voters, and progress on female education and employment opportunities.
Keywords: 300; India; social policies; productive and protective social policies; party competition; clientelism; women's education and formal employment